Justification of the need to Transform the Information Support of the Commercial Real Estate Market of the Republic of Belarus - A. I. Chyhryna (Цифровая трансформация)
The article reveals the shortcomings of existing systems of information support for the commercial real estate market. We have studied the procedures for selecting information about commercial real estate objects, identified their shortcomings, which allowed us to justify the need to transform the current system of information support for the commercial real estate market of the Republic of Belarus. In order to improve the current information support system, it is proposed to achieve these objectives by combining existing databases of technical passports, an automated information system for assessing land in the Republic of Belarus, as well as an automated information system for maintaining the unified state register of real estate, rights to it and transactions with it, in the form of unified technical and economic passports of commercial real estate objects. The introduction of such a document will allow to raise management efficiency as the commercial real estate market segments, and specific commercial properties, to formalize the relationship between the subjects of the commercial property market, and will also act as the basis for increasing economic efficiency and investment attractiveness of commercial real estate market of the Republic of Belarus.